Development of Online-Based Interactive Video Media using Teachmint Application for Natural Science Learning - Sulastiani, Yani; Sholih, Sholih; Rusdiyani, Isti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Many challenges and online learning strategies require educators to innovate and adapt well. The media used so far is less interesting and less interactive. This research was conducted to see the effectiveness of interactive media learning video teachmint application in learning. This study was motivated by the low motivation and learning achievement of students. The learning method is teacher-centred, so learning seems monotonous, and students become passive in participating in learning. The purpose of this study was to describe the feasibility and effectiveness of teachmint application in learning. This research is a research & development (R&D) development, namely 4D which has 4 stages of flow, namely defining (define), designing (design), developing (development), and disseminating (disseminate). The data collection method in this research is by conducting observations, interviews, validation tests of media experts and material experts, questionnaires and pretest and post-test instruments. The results of the media expert validation test obtained a score of 93% with a very feasible category, the material expert test results obtained a score of 77.35% with a very feasible category. While the results of the effectiveness test of the pretest and post-test results with an average Gain Score of 0.74 with high criteria, the student response scored 87.96% of the category strongly agreed, while the teacher response scored an average score of 80% of the category strongly agreed. These results can be concluded that interactive video media with the teachmint application can be declared feasible for use in learning.